Impact of the clip and snare method using the prelooping technique for colorectal endoscopic submucosal dissection - Yamada, Shinya; Doyama, Hisashi; Ota, Ryosuke; Takeda, Yasuhito; Tsuji, Kunihiro; Tsuji, Shigetsugu; Yoshida, Naohiro (Endoscopy, 2016)
Background and study aim: Endoscopic submucosal dissection (ESD) is more difficult to perform for colorectal tumors, but the use of traction to facilitate direct submucosal layer visualization is a promising method to reduce procedure times and complication rates. This study aimed to evaluate the efficacy and safety of the clip and snare method (CSM) with a prelooping technique (PLT) for colorectal tumors.Patients and methods: A total of 140 colorectal tumors were treated: 17 using the CSM with PLT; 123, used as controls, by standard ESD without these techniques. Therapeutic efficacy and safety were retrospectively assessed.Results: All tumors were successfully resected en bloc using the CSM with PLT. Multisegment resection was found in four tumors in the control group. There was a significant difference in the procedure time between the patients in the CSM with PLT group and the control group (45.6 vs. 70.1 minutes; P = 0.047). There were no significant differences in the complication rates (5.9 % vs. 8.1 %; P = 1.00).Conclusions: The CSM with PLT was effective and safe in this study.